Communities That Write: Christ-Groups, Associations, and Gospel Communities - Last, Richard (New Testament studies, 2012)
Critics who posit the ‘gospels for all Christians’ theory contend that gospels reflect neither the history nor the concerns of the communities within which they were produced. Despite advocacy for the theory from an increasing number of scholars, others continue to reconstruct diverse gospel communities. There is some common ground between the two sides of the debate: the majority of scholars from both perspectives agree that gospels were composed within communal settings. If we take this agreement as our starting point and investigate communal writing practices in antiquity, we might productively forge an agreeable method for determining the scope of intended gospel audiences. This study analyzes the collective process of writing in ancient associations, now regarded as analogous in many ways to early Christ-groups. In doing so, a framework is provided for understanding how and to whom gospels produced in Christ-groups might have been composed. The study finds the ‘all Christians’ theory inconsistent with communal practices of writing.